2003
DOI: 10.1016/s1470-0328(02)02105-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer variation in assessment of 845 labour admission tests: comparison between midwives and obstetricians in the clinical setting and two experts

Abstract: Objective To assess the inter-observer agreement in assessment of the labour admission test between midwives and obstetricians in the clinical setting and two experts in the non-clinical setting, the interobserver agreement between two experts in the non-clinical setting and to what degree fetal distress in labour could be predicted by the two experts. Design Observational study.Setting The maternity unit of Hammerfest Hospital, Norway.Population Eight hundred and forty-five high and low risk women.Method The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 8 publications
4
45
1
1
Order By: Relevance
“…Other studies evaluating the reproducibility of CTG analysis using the FIGO and ACOG guidelines have shown that there is a fair to good agreement in evaluation of the baseline and accelerations, and a poor agreement regarding decelerations (3,16). It has also been reported that CTG classification as category I/normal is more reproducible than the other categories (4,5,(17)(18)(19). Our study demonstrates that this depends on the selected guidelines.…”
Section: Discussionsupporting
confidence: 48%
“…Other studies evaluating the reproducibility of CTG analysis using the FIGO and ACOG guidelines have shown that there is a fair to good agreement in evaluation of the baseline and accelerations, and a poor agreement regarding decelerations (3,16). It has also been reported that CTG classification as category I/normal is more reproducible than the other categories (4,5,(17)(18)(19). Our study demonstrates that this depends on the selected guidelines.…”
Section: Discussionsupporting
confidence: 48%
“…The use of CTG is controversial, and its efficacy is being questioned 32,33. However, according to Swedish standards, CTG and FBS are the main tools for the assessment of fetal wellbeing during labour, and it is expected that they will be used 6,34…”
Section: Discussionmentioning
confidence: 99%
“…The false-negative rate for the nonstress test is low ranging from 0.19% to 1%, and when assessing the interobserver variation the proportions of agreement for normal tests were high. 10 In contrast, the false-positive rate of a nonreactive nonstress test is as high as 55%, 11 and the proportions of agreement among experts for equivocal/ominous tests were poor. 10 Given that with an abnormal test result a fetus is more likely to be healthy than compromised, results must be used cautiously by clinicians, particularly at early gestational ages when delivery could result in significant morbidity.…”
Section: Nonstress Test (Nst)mentioning
confidence: 99%